1 Intrinsic vortex formation time: a unique echocardiographic performance indicator. (7th October 2015) - King, G; Neilan, TG; Cohn, K; Gannon, S; Bennet, K; Clarke, J
Abstract : Introduction: Vortex formation time (VFT) is a continuous measure of the left ventricular filling that integrates all phases of diastole and occurs within a dimensionless time T≈ 4. A reduction in VFT can reliably differentiate between healthy control subjects and heart failure patients. 1 Conversely we hypothesised that VFT can be used in the other direction of cardiac health and can vacillate between a transition from normal to supernormal in the athlete and in doing so could act as a cardiac performance indicator in the elite athlete. Methods: We compared echocardiographic indices between n = 41 elite male athletes and n = 22 age, weight and sex-matched sedentary volunteers. VFT was obtained using the validated formula: 4 × (1 − β )/ π × α ³ × LVEF, where β is the fraction of total transmitral diastolic stroke volume contributed by atrial contraction (assessed by time velocity integral of the mitral E- and A-waves) and α is the biplane end-diastolic volume (EDV) 1/3 divided by mitral annular diameter during early diastole. Diastolic myocardial function was measured by the ratio of mitral peak velocity of early filling (E) to early diastolic mitral annular velocity (e') (E/e' ratio) and the ratio of E to mitral peak velocity of late filling (A) (E/A ratio). Multiple regression analysis was used to adjust for heart rate. Results: There was no difference in age, gender, body surface area, systolic or diastolic blood pressure between the controls and athletes. The heart rate was lower (63 ± 10 vs. 74 ± 7 beats per minute, P = 0.001 and the LV was larger in athletes as compared to controls (56 ± 3 vs. 50 ± 4, 0.001). The VFT was lower in the sedentary group as compared to athletes (3.12 ± 0.38 vs. 4.01 ± 0. 80, p < 0.001). Similarly there was a significant difference in E/e ratio between the sedentary (7.5, ±1.8) and athlete (4.18 ± 1.0) groups (p < 0.001). There was a significant correlation between VFT and E/A (r = 0.465, p = 0.0002) but not between VFT and E/e. Conclusion: The VFT is a novel continuous measure of all phases of diastole. The VFT was at the upper threshold limits of dimensionless index of 4 showing optimal vortex formation in athletes compared to controls. The work forms the basis for further research testing the association between VFT and performance measures and whether VFT can differentiate between physiological and pathological cardiac adaptation. Reference: Poh KK, Lee LC, Shen L, Chong E, Tan YL, Chai P, Yeo TC, Wood MJ. Left ventricular fluid dynamics in heart failure: echocardiographic measurement and utilities of vortex formation time. Eur Heart J Cardiovasc Imaging 2012;13(5):385–93